Honey bee colonies performance enhance by newly modified beehives - Abou-Shaara Hossam F.; Al-Ghamdi Ahmad A.; Mohamed Abdelsalam A. (Journal of Apicultural Science, 2013)
Honey bees have good thermoregulation and rapidly respond to any changes in the microclimatic conditions of their colonies. However, colony losses can occur during very cold or hot months. Honey bee colonies are often kept in modified beehives during such times to save the honey bees lives. In the present study, the abilities of four beehive types to enhance the performance of two honey bee races (Carniolan and Yemeni honey bees) were compared under hot and arid environmental conditions. The results indicated performance differences between the two races and between the selected beehive types. For the Carniolan honey bees, better results were obtained in colonies provided with insulated cover boxes (ICB) than in thermoregulatory beehives (TBH), insulated beehives with a back drawer (IBD), and normal beehives (NB) in that order. In contrast, better Yemeni honey bee results were obtained in the TBH, followed by ICB, NB, and finally IBD. Maintaining honey bees in a suitable beehive type is a promising method for saving honey bees lives and enhancing their performance under harsh environmental conditions.